NLP METAMODEL STRATEGY IN CREATIVE COMMUNICATION: FASHION MSMES ON SHOPEE DIGITAL PLATFORM - Azzahrah Andrianti; Siti Aisyah; Rita Hartati (CV. ADIBA AISHA AMIRA, 2025)
This research explored how Neuro-Linguistic Programming (NLP), particularly the Metamodel Language framework, was applied as a communication strategy by fashion Micro, Small, and Medium Enterprises (MSMEs) on the Shopee e-commerce platform. As digital platforms continued to shape modern business practices, effective communication became increasingly vital in influencing consumer trust, perception, and purchasing decisions. The study adopted a mixed-method approach, integrating both qualitative and quantitative techniques to examine language use across 40 communication samples. These samples were taken from product descriptions, responses to customer reviews, and real-time chat interactions. Each sample was categorized into one of four Metamodel language patterns: generalisation, deletion, distortion, or clarification. Findings showed that generalisation appeared most frequently (30%), followed by deletion (25%), while distortion and clarification were equally present (22.5% each). The average frequency across categories was 10.0, with a standard deviation of 1.41, indicating that the distribution of language patterns was relatively consistent. These results suggest that emotionally persuasive yet vague language is commonly used in promotional content, whereas clarification tends to occur more often during direct interaction to resolve uncertainty. Ultimately, the study found that fashion MSMEs on Shopee tended to use a two-fold communication strategy—drawing attention through persuasive language and strengthening consumer confidence through clarification. These insights highlight the practical value of NLP-based communication for digital business and suggest that MSMEs can benefit from balancing emotional engagement with clarity and precision.